2021
DOI: 10.3126/ajms.v12i12.39185
|View full text |Cite
|
Sign up to set email alerts
|

Trends of variation of the laboratory parameters during the course of COVID-19 Illness

Abstract: Background: The coronavirus pandemic which had its origin in the Wuhan China has been spreading across the globe with far reaching complications and a variable clinical course. A variation of the laboratory parameters during the disease course remains a constant parameter to monitor the disease course and progression. Since the laboratory parameters are standardized globally, these may also act as uniform guidelines for the patients monitoring and treatment. Aims and Objectives: The aim of the study was to ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Consistent with this study, other studies found the trend of CRP 9 , 10 , 18 , LDH 10 , 11 , 13 , 18 , PLT 11 , 13 , lymphocyte 8 , 13 , urea 11 , 13 , and Cr can discriminate COVID-19 outcome. Our results fairly confirm results of Burke et al study 13 using dynamic time warping analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with this study, other studies found the trend of CRP 9 , 10 , 18 , LDH 10 , 11 , 13 , 18 , PLT 11 , 13 , lymphocyte 8 , 13 , urea 11 , 13 , and Cr can discriminate COVID-19 outcome. Our results fairly confirm results of Burke et al study 13 using dynamic time warping analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Monitoring and allocating inpatients during peaks of COVID-19 can be challenging. Studies tried to propose laboratory profile for monitoring a hospitalized patient using longitudinal weekly values 9 , comparing early and late results 10 , historical regression tree 11 , Wilcoxon sum rank test of daily averages trend 8 , Mann–Whitney test of daily results between mortality and survived 12 , and dynamic time wrapping analysis 13 . This study used the parallel pairwise comparison to investigate the trend of lab results among survivors and non-survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation